Sensitivity of fine particulate matter concentrations in South Korea to regional ammonia emissions in Northeast Asia - Kim, Eunhye; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Environmental Pollution, 2021)
Ammonia (NH3) is an important precursor for forming PM2.5. In this study, we estimated the impact of upwind transboundary and local downwind NH3 emissions on PM2.5 and its inorganic components via photochemical grid model simulations. Nine sensitivity scenarios with ±50% perturbations of upwind (China) and/or downwind (South Korea) NH3 emissions were simulated for the year 2016 over Northeast Asia. The annual mean PM2.5 concentrations in the downwind area were predicted to change from −3.3 (−18%) to 2.4 μg/m3(13%) when the NH3 emissions in the upwind and downwind areas were perturbed by -50% to +50%. The change in PM2.5 concentrations in the downwind area depending on the change in NH3 emissions in the upwind area was the highest in spring, followed by winter. This was mainly attributed to the change in nitrate (NO3-), a secondary inorganic aerosol (SIA) that is a predominant constituent of PM2.5. Since NH3 is mainly emitted near the surface and vertical mixing is limited during the night, it was modeled that the aloft nitric acid (HNO3)-to-NO3- conversion in the morning hours was increased when the NH3 accumulated near the surface during nighttime begins to mix up within the Planetary Boundary Layer (PBL) as it develops after sunrise. This implies that the control of upwind and/or downwind NH3 emissions is effective at reducing PM2.5 concentrations in the downwind area even under NH3 rich conditions in Northeast Asia.
Keywords: Ammonia emissions; Fine particulate matter; Inorganic components; Planetary boundary layers; PM2.5 concentration; Rich conditions; Secondary inorganic aerosol; Vertical mixing; Ammonia; Long-range transport; Particulate matter; Sensitivity; Vertical mixing